Multi-city study on air pollution and hospital outpatient visits for asthma in China. (February 2020) - Lu, Peng; Zhang, Yongming; Lin, Jiangtao; Xia, Guoxin; Zhang, Wenyi; Knibbs, Luke D.; Morgan, Geoffrey G.; Jalaludin, Bin; Marks, Guy; Abramson, Michael; Li, Shanshan; Guo, Yuming
Abstract: Background: The proportion of asthma patients with mild to moderate exacerbations is far greater than the number who experience episodes that are severe enough to require emergency room visits or hospital admission. However the routinely collected data from hospitals is absent in the past. Objective: To evaluate associations between short-term exposures to air pollutants and hospital outpatient visits for asthma in China. Methods: We obtained data for 143, 057 asthma outpatient visits from the largest hospitals in 17 Chinese cities, between Jan 01 2013 and Dec 31 2015. We used daily concentrations of air pollutants measured by the China National Environmental Monitoring Centre. We used a time-stratified case-crossover design, and fitted conditional logistic regression models to determine the associations. Results: Particulate matter ≤10μm in diameter (PM10) and nitrogen dioxide (NO2) were associated with increased risks of hospital outpatient visits for asthma on the same day, while the effects were delayed for particulate matter ≤2.5μm in diameter (PM2.5) and sulphur dioxide (SO2). For the cumulative effect model at lag05 days, 10 μg/m3 increase in air pollutants concentrations were correlated with hospital outpatient visits for asthma with odds ratios (ORs) and 95% confidence intervals 1.004 (1.000-1.008) for PM2.5, 1.005 (1.002-1.008) for PM10, 1.030 (1.021-1.040) for NO2, and 1.015 (1.008-1.021) for SO2. Almost one in nine (10.9%; 7.7, 13.9%) hospital outpatient visits for asthma were attributable to NO2. Conclusion: Short-term exposures to PM2.5, PM10, NO2 and SO2 were associated with hospital outpatient visits for asthma in China. Graphical abstract: Image 1 Highlights: Air pollution was associated with hospital outpatient visits for asthma in China. PM10 and NO2 were associated with increased risks of hospital outpatient visits for asthma on the exposure day. The effects of PM2.5 and SO2 were delayed. Almost one in nine hospital outpatient visits for asthma were attributable to NO2 .